2017
DOI: 10.3854/crm.7.checklist.atlas.v8.2017
|View full text |Cite
|
Sign up to set email alerts
|

Turtles of the World: Annotated Checklist and Atlas of Taxonomy, Synonymy, Distribution, and Conservation Status (8th Ed.)

Abstract: No overall series subscription rate is available, as individual monograph issues are priced separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
222
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 200 publications
(237 citation statements)
references
References 305 publications
(514 reference statements)
8
222
0
7
Order By: Relevance
“…Our mtDNA results indicated that P. t. tentorius consisted of four clades, each occurring in a different region, generally isolated from each other. Based on morphology, tortoises above the GE in the KHR regions were previously considered to be P. t. trimeni (Boycott & Bourquin, ; Branch, ) but our results confirmed the findings reported in Hofmeyr et al () and Rhodin et al () that these tortoises belong to P. t. tentorius (clade 4). Our sampling showed that P. t. trimeni is only present west of the GE in the WCSK region of South Africa.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our mtDNA results indicated that P. t. tentorius consisted of four clades, each occurring in a different region, generally isolated from each other. Based on morphology, tortoises above the GE in the KHR regions were previously considered to be P. t. trimeni (Boycott & Bourquin, ; Branch, ) but our results confirmed the findings reported in Hofmeyr et al () and Rhodin et al () that these tortoises belong to P. t. tentorius (clade 4). Our sampling showed that P. t. trimeni is only present west of the GE in the WCSK region of South Africa.…”
Section: Discussionsupporting
confidence: 92%
“…Clade 1, C7, and C5 included specimens previously recognized as P. t. tentorius (Boycott & Bourquin, ), whereas C4 comprised individuals previously considered P. t. trimeni but recently identified as P. t. tentorius from the Kamiesberg, Hamtam Karoo and Roggeveldberge (KHR) region of the western Great Escarpment (GE; Rhodin et al, ). Clade 3 included samples of P. t. trimeni from the West Coast Succulent Karoo (WCSK) region (Boycott & Bourquin, ; Rhodin et al, ), and appeared as the sister group of C2, which comprised P. t. verroxii (Boycott & Bourquin, ; Rhodin et al, ) south of the Orange River. Clade 6 also comprised of P. t. verroxii populations, occurring north of the Orange River (NOR), being the sister group of C2 + C3.…”
Section: Resultsmentioning
confidence: 99%
“…Since the mass mortality, it has been formally declared critically endangered by the NSW and Australian governments. It is listed as Data Deficient (under the name Elseya georgesi ) in the IUCN Red List of Threatened Species (http://www.iucnredlist.org), but Critically Endangered in the IUCN/SSC Tortoise and Freshwater Turtle Specialist Group Draft Red List (Rhodin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The PinzĂłn giant tortoise, Chelonoidis duncanensis (previously Chelonoidis ephippium ; Turtle Taxonomy Working Group, ), is endemic to PinzĂłn Island (18 km 2 area) in the Galapagos (Figure ) and consists of a single population. Historically, PinzĂłn giant tortoises numbered in the thousands, but mass harvesting for food by humans in the early to mid‐1800s dramatically reduced the population size (Townsend, ).…”
Section: Introductionmentioning
confidence: 99%